An Analysis of Structure of Argumentation in the Articles of the Jakarta Post Newspaper from 20 August until 22 September 2010 - Maulida Legianti; Alvin Taufik (Journal of English Language and Culture, 2017)
This research analyzes the structure of argumentation used in the articles of the Jakarta Post newspaper from 20 August until 22 September 2010. It also has the purpose to find out the way the journalist constructs the argumentation in his article.This research uses a descriptive method. The researcher takes the data from the articles of the Jakarta Post newspaper dated from 20 August until 22 September 2010. The researcher collects the data using text observation. After that, the researcher analyzes the data using related theories in order to find out the structure of argumentation in the headlines of the Jakarta Post newspaper.After the writer analyzes the data using the related theories, the writer finds each elements of argumentation that exists in the articles of the Jakarta Post newspaper.In conclusion, the structure of argumentation used by the journalist from the Jakarta Post newspaper in the article about terrorism dated from August 20, 2010 until September 22, 2010 can be ordered into: first the journalist gives the probability claims. After that, the journalist provides the second order data and first order data. To make the data and claim related, the journalist gives the authoritative warrants. Then, to advocate the warrant the journalist gives the backing and the qualifiers for the restricted data if the data uses foundation and the claim is not clear and accurate. Keywords: argumentative discourse, structure of argumentation